MANAJEMEN PEMBELAJARAN KITAB KUNING DI PESANTREN SALAFIYAH: - Muhammad Zainal Abidin (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2023)
The teaching of the " Kitab Kuning" in pesantren is an implementation of the function of pesantren as an educational institution as well as a missionary institution. Because it is known, the pesantren tradition is incomplete without the " Kitab Kuning" . Therefore, to maintain the existence of the teaching of the " Kitab Kuning" in pesantren, management of learning becomes the focus that must be developed by pesantren as a comprehensive part of the development of pesantren, this is emphasized because learning management is the key to the success of the learning process in pesantren. The results showed: 1) Empowerment of infrastructure is carried out by a) optimizing the function of learning resources, b) Utilization of learning media and, c) Utilization of infrastructure based on information technology. 2) Empowerment of " Kitab Kuning" learning time is carried out by a) Planning learning time allocation, b) Implementation of learning time allocation and c) Learning time evaluation. 3. Creating a " Kitab Kuning" learning environment is carried out by: a) Revitalizing the Islamic Boarding School Rules, b) Arranging the study room, and c). Building communication between Ustadz - Santri. Keywords: Learning Management, Kitab Kuning , pesantren